2009
DOI: 10.2353/ajpath.2009.080769
|View full text |Cite
|
Sign up to set email alerts
|

Two Different PDGF β-Receptor Cohorts in Human Pericytes Mediate Distinct Biological Endpoints

Abstract: How activation of a specific growth factor receptor selectively results in either cell proliferation or cytoskeletal reorganization is of central importance to the field of pathophysiology. In this study, we report on a novel mechanism that explains how this process is accomplished. Our current investigation demonstrates that soluble platelet derived growth factor-(PDGF)-BB activates a cohort of PDGF-␤ receptors primarily confined to the lipid raft component of the cell membrane, specifically caveolae. In cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Utilizing a proteomics approach followed by colocalization studies, we identified a number of proteins that associate with sFLT1 at the cell surface. Intriguingly, two of the top hits, SCARB1 and ANXA2, are proteins known to associate with lipid rafts-subdomains involved in podocyte actin dynamics and in cytoskeletal reorganization in other pericyte populations (Simons et al, 2001;Sundberg et al, 2009). Along with their location in lipid rafts, these proteins were of interest for other reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing a proteomics approach followed by colocalization studies, we identified a number of proteins that associate with sFLT1 at the cell surface. Intriguingly, two of the top hits, SCARB1 and ANXA2, are proteins known to associate with lipid rafts-subdomains involved in podocyte actin dynamics and in cytoskeletal reorganization in other pericyte populations (Simons et al, 2001;Sundberg et al, 2009). Along with their location in lipid rafts, these proteins were of interest for other reasons.…”
Section: Discussionmentioning
confidence: 99%
“…These receptors were activated by soluble PDGF-B and membrane-bound PDGF-B, which mediate distinct cellular functions. Cytoskeletal reorganization was only induced by soluble PDGF-B (Sundberg et al 2009). The recruitment of pericytes may be determined by the signal balance between the PDGF-B concentration gradient and the localization of PDGFR-b on the cell membrane.…”
Section: Angiogenic Factorsmentioning
confidence: 98%
“…The antiproliferative activity of tacalcitol (Tac), calcipotriol (Cal) and 1a,25(OH) 2 D 3 (1a,25) in T98G cells, measured by manual cell counting. The growth-inhibitory effects were dose-dependent, with the strongest effect at 10 lM.…”
mentioning
confidence: 99%